Uma análise do discurso publicitário em tempos de espetáculo : cenografia e ethos do Itaú na campanha #issomudaomundo - Leite, Rossana Martins Furtado (2015)
Considering that advertising moves the whole society and its subjects and interfer in behavior, identities and cultures, our research aims to understand how the advertising discourse relies on the interdiscourse to compose spectacularized scenographies in order to give a socially responsible institutional ethos to companies such as banco Itaú, which is seen through the analysis of a corpus from #issomudaomundo advertising campaign, in circulation from 2013 to 2015. For methodological reasons, the analysis of this study was divided according to the pillars suggested by the advertising campaign: education, culture and urban mobility. The theoretical perspective used is based on the French Discourse Analysis, in general, with dialogues between theories that make up this discipline, and also with those that served or still serve as theoretical support. The cutting to deepen the analysis is based on the categories of scenography and ethos by Dominique Maingueneau; the work also includes a sociological view of post-modern society, based on theories by M. Sodré (2006), N. Canclini (2010) and Z. Bauman (2001,2009). The results show us that the institutional publicitary discourse has been using scenographies carefully elaborated to create ads associated with ethical socially-responsible worlds which long for touching emotionally consumers who share the same yearnings, consolidating a citizen institutional ethos to the brand 'Itaú' and hiding the commercial / financial senses that are constitutive of it.